SOCIAL ETHICS AND LEARNING ATTITUDES OF FISHERMEN'S CHILDREN IN HAJORAN VILLAGE, SUB-DISTRICT OF PANDAN REGENCY OF CENTRAL TAPANULI - Halimatussakdiah Halimatussakdiah (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
This study aims to obtain data to determine the description of social ethics and attitudes of children in the State Elementary School 152980 Hajoran subdistrict of Pandan regency of  Central Tapanuli. This research method using quantitative descriptive method with survey technique with 25 research samples that come from class V SD Negeri 152980 Hajoran subdistrict of Pandan regency of  Central Tapanuli. Collection techniques data used through surveys by using questionnaires, and Test the validity of the questionnaire using Product Moment correlation coefficient formula while the reliability test using the formula Cronbach Alpha. In this study obtained good criteria data, namely the social ethics of students in the family, social ethics in school and social ethics in the community. And learning attitudes obtained cognitive and affective data have good criteria and psychomotor and learning activities in school and home study activities obtained data with sufficient criteria. Keywords: Social Ethics, Learning Attitude. Children